FOLKLORE AND GREEK HAGIOGRAPHY: SOME PRELIMINARY NOTES. - Gollo, Giulia (Folklore (14060957), 2022)
Based on personal experience and previous academic research, this article aims to lay the foundations for an interdisciplinary approach to Greek hagiography. It represents the first attempt to define the coordinates of the study of ancient hagiographical texts (lives of saints, collections of miracles, praises, etc.) through methodologies from folklore studies. By presenting a concrete example from a collection of miracles of healing dreams, I hope to show the potentialities of such an approach to scholars of my field, who are generally unaware and skeptical of it. At the same time, I would like to outline the richness of data that Greek hagiography has to offer to folklorists. To sum up, mutual exchange is expected (and needed) in the future.